Inappropriate lubricant use with condoms by homosexual men. - Martin, D J (1992)
Use of condoms has been advocated as an important method of reducing the risk of human immunodeficiency virus (HIV) transmission among high-risk groups such as homosexual and bisexual men, prostitutes, intravenous drug users, adolescents, and hemophiliacs. Despite risk-reduction education campaigns directed to gay men since the early 1980s, evidence shows continued deficits in condom-use skills and knowledge among gay men. Because most failures in the use of condoms are attributed to errors in use, increasing knowledge and skills in condom use is important in preventing HIV infection. Two groups of homosexual and bisexual men were sampled, those entering a risk-reduction education program and participants in a Gay Pride event. They were surveyed on their current sex practices and their efforts to reduce their risk of HIV infection. They were asked about their numbers of sex partners, specific sexual behaviors, use of condoms, types of condoms used, and lubricants used for genital-anal sex. The characteristics of those surveyed were similar to those of respondents in other studies of risk reduction among gay men. The use of an oil-based lubricant with condoms has been shown to weaken latex and to increase the likelihood of condom breakage, which use of water-based lubricants does not. Among respondents who reported having genital-anal sex, 60 percent reported use of an oil-based lubricant with a condom at least once during the year before the survey. Gay men in sexually exclusive relationships engaged in less consistent use of condoms for receptive genital-anal sex than did single gay men.(ABSTRACT TRUNCATED AT 250 WORDS)